Biosolids as an Alternative Fertilizer for Kentucky Bluegrass Sod Production in Wisconsin. (16th August 2017) - Griffith, Shane; Bero, Nicholas; Stier, John; Obear, Glen; Ruis, Sabrina; Soldat, Douglas
Abstract : Land application of biosolids holds the potential to reduce or eliminate the need for synthetic fertilizer applications. The objective of this study was to evaluate the agronomic impacts of using biosolids to produce Kentucky bluegrass ( Poa pratensis L.) sod on a silt loam soil in Wisconsin. Anaerobically digested biosolids cake and biosolids cake mixed with sand and sawdust in a 2:1:1 ratio by volume (MetroMix TM ) were produced by and obtained from the Madison Metropolitan Sewerage District. Each material was applied at three rates based on their estimated supply of plant‐available nitrogen (PAN). The control treatment mimicked conventional sod maintenance techniques using synthetic fertilizer applied at 309 kg N ha −1 over the 20‐mo production cycle. All biosolids treatments improved or exhibited similar establishment cover compared with the conventional practice. However, generally the lowest rate of cake and the two lowest rates of the MetroMix underperformed the conventional production in terms of visual quality throughout harvest and into transplanting. Cake had superior visual quality compared with MetroMix when applied at equivalent PAN rates. Optimization modeling determined that a biosolids cake application rate of 425 kg PAN ha −1 would likely meet agronomic standards (quality, color, sod strength, etc.) of the conventional practice. Repeated applications decreased the optimized biosolids rate to from 425 to 325 and 285 kg PAN ha −1, depending on number of previous applications. These results suggest that biosolids‐based sod production has the potential to replace or supplement traditional fertilization practices to meet current agronomic goals for sod production in Wisconsin.